2014
DOI: 10.3389/fpsyg.2014.00241
|View full text |Cite
|
Sign up to set email alerts
|

Eye-closure increases children's memory accuracy for visual material

Abstract: Research shows that closing the eyes during retrieval can help both adults and children to remember more about witnessed events. In this study, we investigated whether the eye-closure effect in children is explained by general cognitive load, modality-specific interference, or a combination. 120 children (60 female) aged between 8 and 11 years viewed a 5-min clip depicting a theft and were questioned about the event. During the cued-recall interview, children either viewed a blank screen (blank-screen conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…It is quite possible that even though 'eye closure' combined with 'questioning' can sometimes improve recall (Gudjonsson, 1992;Vredeveldt et al, 2015), such effects are not strong enough to be significant when tested only for the second recall attempt where the number of recalled units of information is somewhat small, in comparison with the number of recalled details throughout the whole interview. Furthermore, for the purpose of conducting adequate investigative interviews, the interviewer allowed two participants to spontaneously use 'eye closure' in the RECI1 condition, and always tried to reduce to a minimum all possible auditory and visual distractions in the interview environment for all interview conditions which research suggests that may be as effective as 'eye-closure' (Mastroberardino & Vredeveldt, 2014;Vredeveldt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is quite possible that even though 'eye closure' combined with 'questioning' can sometimes improve recall (Gudjonsson, 1992;Vredeveldt et al, 2015), such effects are not strong enough to be significant when tested only for the second recall attempt where the number of recalled units of information is somewhat small, in comparison with the number of recalled details throughout the whole interview. Furthermore, for the purpose of conducting adequate investigative interviews, the interviewer allowed two participants to spontaneously use 'eye closure' in the RECI1 condition, and always tried to reduce to a minimum all possible auditory and visual distractions in the interview environment for all interview conditions which research suggests that may be as effective as 'eye-closure' (Mastroberardino & Vredeveldt, 2014;Vredeveldt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“… It is also known that recalling an image with closed eyes might be preferable for some of us. This effect has not yet been fully understood 21 , 22 , and has posted a challenge in practice for eye movement recording using video-based eye trackers. Many previous studies consistently reported that eye movements while looking at nothing contain a large distortion due to the lack of reference frame.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that recalling an image with closed eyes might be preferable for some of us. This effect has not yet been fully understood 21 , 22 , and has posted a challenge in practice for eye movement recording using video-based eye trackers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established eye-closure as an effective method to aid memory retrieval (e.g., Perfect et al, 2008 ; Mastroberardino et al, 2012 ; Mastroberardino and Vredeveldt, 2014 ) and to improve performance on mathematical queries and general-knowledge questions ( Glenberg et al, 1998 ), arguably because eye-closure effectively reduces interference from external stimulation. A similar mechanism is considered to be responsible for gaze aversion, that is, the phenomenon that people direct their gaze away from salient stimuli such as the eyes of a conversation partner, when they engage in a cognitively demanding task such as memory retrieval ( Glenberg et al, 1998 ; Phelps et al, 2006 ; Doherty-Sneddon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%